Forgotten Theorists of Lithuanian Romanticism: Priest Ignotas Dembinsky - Viliūnas, Dalius (Problemos, 2021)
The sluggish development of romantic philosophy research suggests looking back at new sources that have been ignored so far. Priest Ignacy Dembinsky (1800–1869) is a forgotten romantic theorist. He is not only Wilhelm Schlegel’s translator, but also his promoter, commentator, who formulated authentic insights of romantic philosophy. The article focuses on the circumstances of Schlegel’s two-dimensional publication of “Philosophy of Life” (1840), which remained on the subscriber list, raises the hypothesis that the subscription of the work was a large-scale quasi-political patriotic campaign. The direction represented by Dembinsky is attributable to legal catholic romanticism. The latter sought to establish a positive alternative to Enlightenment’s scientism, naturalism, sensualism, one-sided rationalism, based on ideas of compatibility between science and philosophy, philosophy and Revelation. A person should realize freedom in a moral life and strive for the fullness of life – these ideas had refreshing sociopolitical implications in a depressing tsarist reality. Dembinsky polemicized with his local competitor, Florian Bochvic, a representative of a similar direction. The latter episode raises the question of the compatibility of his catholic theological doctrine and his maxims of a romantic philosopher: it is left open. It is hypothesized that the works translated, commented and creatively supplemented by Dembinsky could function as a bridge between the old Polish-speaking philosophy of Lithuania and the beginnings of the current Lithuanian theorization.